(untitled) (Medicine Today, 2020)
Introduction:Coronavirus is a highly infectious contagious virus producing pandemic throughout the world with highmorbidity and mortality. Discussion: Right now, there is no vaccine to prevent human coronavirus infections. But you mayable to reduce your risk of getting or spreading an infection by-washing hands often with soap and water for at least 20seconds, use an alcohol-based hand sanitizer that contains at least 70% alcohol if soap and water are not available. Avoidingtouching your face, nose, or mouth with unwashed hands, use of face mask, avoiding close contact with people who aresick, there is no specific treatment for coronavirus. Conclusion:Treatment aims to relieve the symptoms. Most people willget better on their own. However, you can relieve your symptoms by-taking over-the-counter medicines for pain, fever, andcough. Using a room humidifier or taking a hot shower to help ease a sore throat and cough. Getting plenty of nutritiousdiet, drinking fluids and taking rest. Medicine Today 2020 Vol.32(2): 138-142